In INVENTARISASI TUMBUHAN OBAT TRADISIONAL SEBAGAI UPAYA SWAMEDIKASI OLEH MASYARAKAT SUKU TORAJA KABUPATEN TORAJA UTARA - Alang, Hasria; Ayu, Ester; Rahmadani, St. (Jurnal Farmasi Udayana; Vol. 11, No. 2, Tahun 2022DO - 10.24843/JFU.2022.v11.i02.p05, 2023)
The Toraja people have been using plants as medicine for their health since time immemorial, but the tribal medicinal plant inventory has never existed. The results of this study are expected to add references to plant species that can act as traditional medicines so that this knowledge can be known by future generations, and can also contribute knowledge, so that research related to traditional medicines for public health can continue to be developed. This study aims to determine the types of medicinal plants, the parts used, and how to process these medicinal plants. This research was conducted in six six villages namely Rura Village, Penanian Village, Singki' Village, Pasele Village, Karassik Village, and Saloso Village, in Rantepao District. The method used is a survey, data collection through interviews and observations. Data analysis was done descriptively. The results of the study found that there were 20 types of medicinal plants used by the Toraja people in Rantepao District as traditional medicines. Most types of medicinal plants come from the Zingiberaceae and Euphorbiaceae families. The most widely used medicinal plant part is the leaf, and the least part is the fruit flesh. The processing of medicinal plants is done by boiling, mashing and sticking them, and eating them directly. Conclusion: Toraja people in the study area use plants as traditional medicine